Ahmadiyah di Era Reformasi - Saipul Hamdi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2011)
This article examines the complexities surrounding violence by Muslims towards the Ahmadiyya community in Indonesia in its new era of democracy. Violence emerged in 1998 in the post-Suharto era when some Muslim groups, such as Front Pembela Islam (FPI), claimed that Ahmadiyya is a deviant group (aliran sesat) according to Islamic orthodoxy. This article works to understand why and how Ahmadiyya became a target of violent attacks by some Muslim groups in the post-Suharto era by considering the rise of Islamic fundamentalist groups during this time of new-found religious freedom. In doing so, I ask how politics, economy and Islamic theology emerged as significant factors that contributed to the attack. Through identifying particular case studies of attacks in cities across Java and Lombok, I also explore how government creates the policy to find the best solution and how far the effectiveness of this policy to solve the problem.